In Vitro Antioxidant Properties, Glucose-Diffusion Effects, α-Amylase Inhibitory Activity, and Antidiabetogenic Effects of C. Europaea Extracts in Experimental Animals - Hayat Ouassou; Mohamed Bouhrim; Noureddine Bencheikh; Mohamed Addi; Christophe Hano; Hassane Mekhfi; Abderrahim Ziyyat; Abdekhaleq Legssyer; Mohamed Aziz; Mohamed Bnouham (MDPI AG, 2021)
Caralluma europaea (Guss.) N.E.Br. (C. europaea), is a medicinal plant used traditionally to treat diabetes mellitus (DM) in Morocco. This study aimed to investigate the in vitro antioxidant properties, glucose diffusion effects, α-amylase inhibitory activity, and pancreatic protective effects of C. europaea in experimental alloxan-induced diabetes in mice. Total phenolic contents were determined by Folin-Ciocalteu colorimetric method, total flavonoid contents were measured by aluminum chloride colorimetric assay, and tannins contents were determined by employing the vanillin method. C. europaea ethyl acetate fraction exhibited high antioxidant potential in terms of radical scavenging (DPPH) (IC50 = 0.22 ± 0.01 mg/mL), β-carotene bleaching activity (IC50 = 1.153 ± 0.07 mg/mL), and Ferric-reducing antioxidant power. Glucose diffusion was significantly inhibited by the ethyl acetate fraction at 60,120and 180 min, while the aqueous extract did not have this inhibitory effect when compared with the control group. Potent α-amylase inhibitory activity was observed in the ethyl acetate fraction and the aqueous extract in vitro and in vivo using STZ-diabetic rats. On the other hand, the administration of the ethyl acetate fraction (60 mg/kg) significantly attenuated alloxan-induced death and hyperglycemia in treated mice. Furthermore, histopathological investigations revealed that the ethyl acetate fraction protected islets of Langerhans against alloxan-induced tissue alterations. These results suggest that C. europaea exhibited an important antihyperglycemic effect via the inhibition of glucose diffusion and pancreatic α-amylase activity. In addition, the antidiabetogenic effect of C. europaea might be attributed to their polyphenol and flavonoid compounds, which could be reacted alone, or in synergy, to scavenge the free radicals produced by the alloxan.